2016
DOI: 10.2337/db15-1423
|View full text |Cite
|
Sign up to set email alerts
|

β-Lapachone Prevents Diet-Induced Obesity by Increasing Energy Expenditure and Stimulating the Browning of White Adipose Tissue via Downregulation of miR-382 Expression

Abstract: There has been great interest in the browning of fat for the treatment of obesity. Although b-lapachone (BLC) has potential therapeutic effects on obesity, the fat-browning effect and thermogenic capacity of BLC on obesity have never been demonstrated. Here, we showed that BLC stimulated the browning of white adipose tissue (WAT), increased the expression of brown adipocyte-specific genes (e.g., uncoupling protein 1 [UCP1]), decreased body weight gain, and ameliorated metabolic parameters in mice fed a high-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Therefore, we proposed that increased expression of miR-382 may promote LPCs differentiation. Occasionally, according to previous reports, miR-382 affect various lineage conversion, including adipocytes differentiation [32], osteogenic differentiation [33] and hematopoietic stem cell differentiation [34]. Together with our findings, we speculate that miR-382 is always involved in various stem cell differentiation.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, we proposed that increased expression of miR-382 may promote LPCs differentiation. Occasionally, according to previous reports, miR-382 affect various lineage conversion, including adipocytes differentiation [32], osteogenic differentiation [33] and hematopoietic stem cell differentiation [34]. Together with our findings, we speculate that miR-382 is always involved in various stem cell differentiation.…”
Section: Discussionsupporting
confidence: 57%
“…We found that the expression of Dio2 and PPARγ was increased in the epididymal fat of CTS-, COST-, and COSM-treated rats compared with the rats in the HF group ( Supplementary Figure S2D,E). Another argument is that Dio2 and PPARγ also play an important role in promoting browning [36], as PPARγ is essential for maintaining WAT and BAT differentiation [37] and Dio2 activation promotes adrenergic response and energy expenditure [38].…”
Section: Discussionmentioning
confidence: 99%
“…miR-378 is increased during brown adipocyte differentiation, promoting brown adipogenesis and protecting against both genetic and high-fat diet-induced obesity. Upregulation of miR-382 inhibited beige differentiation of mice WAT stromal vascular fractions, thereby reducing UCP1 mRNA and protein levels (18). On the other hand, miR-196a induced the beigening of mice WAT with characteristic appearance and gene expression profile of brown adipocytes (Prdm16 and Ucp1) (74).…”
Section: Mirs Involved In Nonshivering Thermogenesismentioning
confidence: 99%